Post-Surgical Recovery Through Multidisciplinary Collaboration: The Integral Roles of Physical Therapy, Social Services, and Pharmacy in Optimizing Patient Outcomes - Alrogy, Majed Abdullah; Alalawi, Fahad Abdulfattah Ali; Asiri, Mohammed Yahya Ahmed; Aljahbani, Mohmmad Nasser; Alghadhbani, Awadh Ayeydh; Alazzmi, Abdullah Ali; Alazmi, Saad Ibrahim; Asiri, Ahmed Ali Hadi; Balharth, Fatemah Hussin; Albar, Ohud Hamed; Hakamy, Ahmad Hafed; Essa , Abdulaziz Ali Al Bin; et al. (Journal of Ecohumanism, 2024)
Background: Post-surgical recovery is a complex process influenced by various factors, including pain management, nutritional status, and multidisciplinary collaboration. Effective management strategies are vital for enhancing patient outcomes, minimizing opioid use, and addressing the psychological aspects of recovery. Methods: This review synthesizes current literature on the collaborative roles of physical therapy, social services, and pharmacy in optimizing recovery in post-surgical patients. A systematic search was performed across databases such as PubMed, CINAHL, and Scopus, focusing on studies published between 2018 and 2023 that examined pain management strategies, nutritional interventions, and the impact of multidisciplinary teamwork. Results: The findings indicate that a multidisciplinary approach significantly improves post-surgical recovery. Collaborations among physical therapists, social workers, and pharmacists enhance pain control, promote nutritional optimization, and support patients' psychological well-being. Non-pharmacological pain management strategies, including physical therapy and psychological interventions, were shown to reduce reliance on opioids while improving overall patient satisfaction. Conclusion: Integrating physical therapy, social services, and pharmacy into post-surgical care fosters a holistic approach that addresses the multifaceted needs of patients. This collaboration not only enhances recovery outcomes but also promotes sustainable pain management practices. Future research should focus on establishing standardized protocols to further enhance the effectiveness of multidisciplinary teams in surgical recovery settings